Role of Acute Symptomatic Seizures and Hippocampal Sclerosis in Development of Post-Stroke Epilepsy - Adnan Mahmood, Muhammad Imran Khan, Rashid Imran, Mohsin Ahmad, Adnan Tariq, Muhammad Fateen Rashed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze the risk and role of acute symptomatic seizure and hippocampal sclerosis in the development of post-stroke epilepsy. Study Design: Retrospective study. Place and duration of study: Department of Neurology, Gujranwala Medical College, Gujranwala from 1st July 2021 to 31st December 2021. Methodology: One hundred patients were enrolled on the basis of acute ischemia or hemorrhagic stroke occurrence. These two conditions were confirmed through MRI imaging. Atrophy formation, alterations in signals visibility in T1 as well as T2 weighted-sequences in addition to internal architecture loss with atrophy of hippocampal was the MRI criteria for diagnosis of hippocampal sclerosis. A control group was also generated of fifty patients to assess the clinical diagnostics of hippocampal sclerosis patients against normal controls. Results: There were 57% males and 43% females with a mean age of 74.2±13.2 years. Ischemia was seen in 40% of the cases while hemorrhagic stroke was present in 62% of all the patients enrolled. Acute symptomatic seizures were present in 30 cases while it was not observed in 70 other cases. The EEG of hippocampal sclerosis presented fronto-parietal stroke and left parieto-temporal strokes while in controls with majority as cerebral venous sinus thrombosis, in addition to basal ganglia hemorrhage. Conclusion: Acute hemorrhage from stroke in combination with the acute and symptomatic seizure results into epileptic episodes and in many cases to secondary formation of hippocampal sclerosis. Keywords: Acute symptomatic seizures (ASS), Hippocampal sclerosis, Post-stroke epilepsy